Acompanhamento a educadoras de berçário - atuando na interface entre saúde e educação - Patuzzi, Arthur; Nagel Pinho, Gabriela; Lindemann Kunzler, Luíse; Sant’Ana Vargas, Felipe; Ferrari, Andrea Gabriela; da Rosa Silva, Milena; de Conti, Luciane; Bicca Charczuk, Simone; Prates Dantas, Cândida; Tenório Brito de Oliveira, Maria Eduarda (Revista da Extensão, 2024)
Acompanhamento a educadoras de berçário - atuando na interface entre saúde e educação